Florida Crop/Pest Management Profile: Cabbage - Wael M. Elwakil; Mark Mossler (EDIS)
Florida’s cabbage production is exclusively for the fresh market. The higher-quality cabbage obtained during the late fall, winter, and early spring months in Florida allows the shipment of fresh cabbage to areas of the United States that cannot produce cabbage during that part of the year. This 18-page fact sheet summarizes production practices and pest management for cabbage production in Florida. Written by Wael M. Elwakil and Mark Mossler, and published by the UF Department of Agronomy, April 2013.